1995
DOI: 10.1051/rnd:19950605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17β-estradiol on calcitonin and calcitonin-gene-related peptide secretions and contents in a murine medullary thyroid carcinoma C-cell line (CA-77)

Abstract: Summary ― The effect of 17!-estradiol on calcitonin (CT) and calcitonin-gene-related peptide (CGRP) secretions in the murine CA-77 C cell line was studied after 1, 3, 5 and 6 d of treatment. The release of both CT and CGRP significantly increased 1, 3, 5 and 6 d after addition of 0.1 Ilmol/l estradiol alone to the culture medium. The C cell content of both peptides also increased after 6 d of treatment with the same dose of estrogen. The enhanced CT and CGRP secretions induced by 17(3-estradiol were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Co-treatment of CA-77 C cells by dexamethasone and 9-cis retinoic acid reduced the usual increase in the release of both CT (Lamari et al, 1994). A slight decrease in the release of both hormones in the culture medium was observed with a lower dose (5 pM) after 6 days of exposure to all-tran.s retinoic acid (Lamari et al, 1995). The present results demonstrated that CA-77 cells are also sensitive to 9-cis retinoic acid since the release of both CT and CGRP were decreased with a half-effective dose of 10 nM.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Co-treatment of CA-77 C cells by dexamethasone and 9-cis retinoic acid reduced the usual increase in the release of both CT (Lamari et al, 1994). A slight decrease in the release of both hormones in the culture medium was observed with a lower dose (5 pM) after 6 days of exposure to all-tran.s retinoic acid (Lamari et al, 1995). The present results demonstrated that CA-77 cells are also sensitive to 9-cis retinoic acid since the release of both CT and CGRP were decreased with a half-effective dose of 10 nM.…”
Section: Resultssupporting
confidence: 49%
“…Intra-assay variations for the CT RIA were 5% and inter-assay variations were 10%. For the CGRP, the RIA used has been described previously (Maubras et al, 1993;Lamari et al, 1995 The bound to free fractions were separated by adding 0.15 mL of dextran charcoal suspension buffer to each assay tube (0.5 mL). After centrifugation at 2 000 g for 20 min, the supernatant was discarded.…”
Section: Radioimmunoassays (Ria S )mentioning
confidence: 99%
“…Intra-assay variations for the CT RIA were 5°/,, and inter-assay variations were 10%. For the CGRP RIA already described [14,15], we have used synthetic human CGRP (Sigma) as standard, a sheep antibody raised against synthetic human CGRP diluted 1 : 100 000, and [125I]iodohistidyl human CGRP from Amersham (Les Ulis, France). The tubes were preincubated for 4 days at 4°C and then incubated for 3 days at 4°C in the presence of labeled CGRP.…”
Section: Radioimmunoassays (Rias)mentioning
confidence: 99%